2006
DOI: 10.1007/s00125-006-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

The threshold for diagnosing impaired fasting glucose: a position statement by the European Diabetes Epidemiology Group

Abstract: The category of IFG was introduced in the late 1990s to denote a state of non-diabetic hyperglycaemia defined by a fasting plasma glucose (FPG) concentration between 6.1 and 6.9 mmol/l. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 33 publications
0
63
0
3
Order By: Relevance
“…The DECODE (Diabetes Epidemiology: Collaborative analysis of Diagnostic criteria in Europe) study group also found that the 7-year risk of coronary heart disease was lower in women with a fasting glucose value between 5.6 and 6.0 mmol/l compared with women with NFG (20). Because of such findings, the lower cutoff of the 2003 ADA criteria for IFG has been questioned (21,22). This reported J-shape and the results of the present study are strong reasons to reconsider the recommendation to lower the IFG cutoff to 5.6 mmol/l.…”
Section: Consequences Of Lowering the Ifg Cutoff For Cvd Riskmentioning
confidence: 62%
“…The DECODE (Diabetes Epidemiology: Collaborative analysis of Diagnostic criteria in Europe) study group also found that the 7-year risk of coronary heart disease was lower in women with a fasting glucose value between 5.6 and 6.0 mmol/l compared with women with NFG (20). Because of such findings, the lower cutoff of the 2003 ADA criteria for IFG has been questioned (21,22). This reported J-shape and the results of the present study are strong reasons to reconsider the recommendation to lower the IFG cutoff to 5.6 mmol/l.…”
Section: Consequences Of Lowering the Ifg Cutoff For Cvd Riskmentioning
confidence: 62%
“…We obtained venous plasma samples at 0, 30, 60, 90 and 120 min for determination of plasma glucose and insulin. Glucose tolerance was evaluated based on OGTT as follows: NGT (fasting glucose <5.6 mmol/l and 2 h glucose <7.8 mmol/l); isolated IFG (fasting glucose 5.6-6.9 mmol/l and 2 h glucose <7.8 mmol/l); isolated IGT (fasting glucose <5.6 mmol/l and 2 h glucose 7.8-11.0 mmol/l); and IFG+IGT (fasting glucose 5.6-6.9 mmol/l and 2 h glucose 7.8-11.0 mmol/l) [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…This change has been contentious and has not been accepted by all organizations (19,38 ). The rationale is based on data that individuals with FPG values between 5.6 mmol/L (100 mg/dL) and 6.05 mmol/L (109 mg/dL) are at increased risk for developing type 2 diabetes (39,40 ).…”
Section: B the Nacb Recommends Adoptionmentioning
confidence: 99%